IUTAM Symposium on Turbulence in the Atmosphere and Oceans Proceedings of the IUTAM Symposium on Turbulence in the Atmosphere and Oceans, Cambridge, UK, December 8 12, 2008 - Dritschel, David. (IUTAM Bookseries, 2010)
This book stems from the IUTAM symposium Rotating Stratified Turbulence and Turbulence in the Atmosphere and Oceans which took place at the Isaac Newton Institute for Mathematical Sciences in Cambridge from 8 to 12 December 2008, and came at the end of a four-month Programme on High Reynolds Number Turbulence . This symposium, widely attended by researchers from around the world, aimed to better understand the complex nature of fluid flows found in Nature, particularly in the Earths atmosphere and oceans, but also in other planetary atmospheres and in the Suns interior. Talks covered a broad range of subjects, from theoretical studies of fundamental vortex interactions, to laboratory experiments and observations, and to state-of-the-art computational studies. The present volume presents a cross-section of the research presented at the symposium, or in some cases, of the research inspired by it. Herein, 23 peer-reviewed papers are collected (39 talks were presented). The research is loosely divided into four main topics: (1) Waves and Imbalance, (2) Turbulence and Convection, (3) Instability and Vortex Dynamics, and (4) Jets: Formation and Structure.